직접 메탄올 연료전지용 메탄올 센서의 백금 두께의 변화에 따른 전류-전압 특성 변화 - 양진석; 김성일; 김춘근; 박정호 (한국마이크로전자및패키징학회, 2007)
We have fabricated methanol sensor for monitoring the methanol concentration in direct methanol fuel cells. A thin composite nafion membrane was used as an electrolyte. We have analyzed the I-V characteristic of the fabricated methanol sensor as functions of methanol concentration, catalyst electrode and platinum (Pt) thickness. When we measured the sensor with 10 nm Pt and at 1 V, the current value was 1.30 x 10(-6), 1.96 x 10(-6), and 2.80 x 10(-6) A for three methanol concentration of 1, 2, and 3 M, respectively. And when the methanol concentration was fixed at 2 M, the current value of the fabricated device with Pt of 5, 10 and 15 nm was 3.06 x 10(-6), 1.96 x 10(-6), and 1.00 x 10(-6) A, respectively. (C) 2008 Published by Elsevier Ltd.